Spinal cord ischemia complicating treatment of abdominal aortic aneurysms: a legal overview: A rare complication of abdominal aortic surgery and its legal consequences - Basile, Giuseppe; Ghezzi, Marcello; Rinaldi, Luigi Federico; Brioschi, Chiara; Passeri, Alberto; Giorgetti, Arianna; Marone, Enrico Maria (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Spinal cord ischemia following open or endovascular aneurysm repair of the abdominal aorta is rare but highly disabling complication. The aim of this work is to report on its occurrence and its legal consequences. Methods: We report a case of spinal cord ischemia complicating an endovascular aortic repair, its management and sequalae, comparing it with the existing literature and we examine its legal consequences resulting in a malpractice lawsuit and the final decision of the judge. Results: Although the causal relation between SCI and the neurological deficits reported were assessed by the Court, no element of responsibility imputable to the Hospital or the Medical Staff were found, since the defendant had made every effort to prevent it in the preoperatory setting, and to treat it once it established in the post-operative phase. Conclusions: predictable but unpreventable complications of necessary interventions rule out medical malpractice, as long as the patient is fully informed about the risks and benefits of the treatment, and provided that in the perioperative setting all due measures are taken in order to prevent it and treat it.